Spiritualitas Bisnis dalam Keberlanjutan Usaha Kuliner Muslim yang Bertahan Lebih dari 5 Tahun di Kelurahan Bumi Ayu, Kota Bengkulu - Teyensi; Nurul Hak; Uswatun Hasanah (Universitas Muhammadiyah Surabaya, 2026)
This study aims to analyze the implementation of Islamic business spirituality and its role in supporting the sustainability of Muslim culinary businesses that have survived for more than five years in Bumi Ayu Village, Bengkulu City. This research employed a field research method with a qualitative descriptive case study approach. Informants were selected using purposive sampling techniques involving business owners, employees, and customers from three Muslim culinary businesses. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that Islamic business spirituality values such as tauhid (monotheism), tawakal (trust in God), amanah (trustworthiness), ṣidīq (honesty), ihsan (excellence), gratitude, and patience had been implemented in daily business practices. These values were reflected in maintaining product quality and halal standards, transparent transactions, friendly services, and harmonious working relationships. Furthermore, Islamic business spirituality played a significant role in strengthening business sustainability through increasing customer loyalty, operational stability, positive social relationships, and selective business adaptation without losing the business’s core identity. Therefore, Islamic business spirituality not only has a religious dimension but also serves as a strategic foundation for achieving the economic, social, and moral sustainability of Muslim culinary businesses. Keywords: Islamic business spirituality, business sustainability, Muslim culinary business, MSMEs, Islamic business ethics.